Antinociceptive Interaction of (±)-Cpp and Propentofylline in Monoarthritic Rats - Hernandez-Kunstmann, A; Laurido-Fuenzalida, C; Constandil-Cordova, L (2012)
Introduction: Multiple studies have shown that glial cells of the spinal cord, such as astrocytes and microglia, have close contact with neurons, suggesting the term tripartite synapse. In these synapses, astrocytes surrounding neurons contribute to neuronal excitability and synaptic transmission, thereby increasing nociception and thus the persistence of chronic pain. Conversely, the N-methyl-D-aspartate (NMDA) receptor is crucial in the generation and maintenance of chronic pain. It has multiple sites of modulation. One is the site of recognition of extracellular neurotransmitter (glutamate), which can be blocked by competitive antagonists such as (3-(2-carboxipiperazin-4)1-propyl phosphonic acid), (±)-CPP, resulting in a blockade of the calcium current and thus the intracellular transduction process. In the present study, we investigated whether the potential antinociceptive effect of glial inhibition produced by propentofylline (PPF) can be enhanced when combined with an NMDA-receptor inhibitor such as (±)-CPP.Methods: We used Sprague-Dawley monoarthritic rats. The monoarthritis was induced by injection of complete Freund adjuvant in the right tibiotarsal joint. Four weeks later, rats were treated with PPF (1, 10, 30, and 100 ?g/10 ?l) intrathecally (i.t.) for 10 days, injected once with (±)-CPP (2.5, 5, 12.5, 25, 50, and 100 ?g/10 ?l, i.t.), or both treatments combined. The antinociceptive effect was evaluated on day 11 for PPF and immediately to (±)-CPP, by assessing the vocalization threshold to mechanical stimulation of the arthritic paw.Results: The data indicate that intrathecal administration of increasing concentrations of (±)-CPP or PPF produced a significant dose-dependent antinociceptive effect with respect to monoarthritic rats receiving saline. The linear regression analysis showed that the dose that produces 30% of maximal effect (ED30) for i.t. (±)-CPP was 3.97 ?g, and 1.42 ?g for i.t. PPF. The administration of the PPF and (±)-CPP combination in fixed proportions of ED30produced a dose-dependent antinociceptive effect, showing an interaction of the supraadditive type.Conclusions: The results suggest that glia inhibitors can synergically potentiate the effect of glutamate blockers for the treatment of chronic inflammatory pain. © 2012 Morales et al.; licensee BioMed Central Ltd.